2014
DOI: 10.1016/j.jaip.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Fever, Rash, and Systemic Symptoms: Understanding the Role of Virus and HLA in Severe Cutaneous Drug Allergy

Abstract: Drug hypersensitivity syndromes such as abacavir hypersensitivity and the severe cutaneous adverse drug reactions (SCAR) have been associated with significant short and long-term morbidity and mortality. More recently these immunologically mediated and previously unpredictable diseases have been shown to be associated with primarily Class I and also Class II HLA alleles. The case of the association of HLA-B*57:01 and abacavir hypersensitivity has created a translational roadmap for how this knowledge can be ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 162 publications
(76 reference statements)
2
44
0
4
Order By: Relevance
“…89 Several insights of importance for diagnosis and potential future management of drug allergy were reported. HLA associations with adverse drug reactions are well described, 90 but Gueant et al 91 have now identified HLA-DRA variants predicting penicillin/amoxicillin allergy but not cephalosporin allergy. Insight into the mechanism of keratinocyte apoptosis in patients with toxic epidermal necrolysis (TEN) was noted in a study of microRNAs extracted from tissues and sera of patients and through supporting in vitro studies.…”
Section: Drug Allergymentioning
confidence: 99%
“…89 Several insights of importance for diagnosis and potential future management of drug allergy were reported. HLA associations with adverse drug reactions are well described, 90 but Gueant et al 91 have now identified HLA-DRA variants predicting penicillin/amoxicillin allergy but not cephalosporin allergy. Insight into the mechanism of keratinocyte apoptosis in patients with toxic epidermal necrolysis (TEN) was noted in a study of microRNAs extracted from tissues and sera of patients and through supporting in vitro studies.…”
Section: Drug Allergymentioning
confidence: 99%
“…However, this system did not include HHV-6 reactivation, which is not a feature of other adverse drug reactions, making its detection a sensitive and specific marker for the diagnosis of DIHS. Based on this, an updated diagnostic tool with nine parameters was developed by a Japanese consensus group (J-SCAR), with the requirement of at least seven to identify DRESS [26] (Table 3).…”
Section: Statins-atorvastatinmentioning
confidence: 99%
“…HLA-B*5701, HLA-B*5801, HLA-B*1502, HLA-A*3101, HLA-A*0206, HLA-B*4403, HLA-A29, HLA-B12, HLA-DR7, and HLA-A2 are linked to SJS drug hypersensitivity reactions. [38][39][40][41] HLA-DQB1*0601, HLA-DQA1*0103, DQB1*0301, and HLA-A*0206 are linked to ocular manifestations in SJS. 42 Genetic influences can explain why SJS occurs in multiple family members even though it is a rare condition 43 or why it recurs in certain individuals.…”
Section: Genetic Predispositionmentioning
confidence: 99%